2000
DOI: 10.1021/jo9912754
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Metal Ion Complexation Studies of Proton-Ionizable Calix[4]azacrown Ethers in the 1,3-Alternate Conformation

Abstract: A series of novel N-chromogenic calix[4]arene azacrown ethers were synthesized as selective extractants of potassium ion. 1,3-Alternate calix[4]arene azacrown ethers were prepared by reacting 25,27-dipropyloxy-26,28-bis(5-chloro-3-oxapentyloxy) calix[4]arenes with p-toluenesulfonamide in the presence of potassium carbonate. The coupling reaction of calix[4]arene azacrown ether with 2-hydroxy-5-nitrobenzyl bromide in the presence of triethylamine in THF gave the chromogenic calix[4]arene azacrown ether in moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 28 publications
2
54
0
Order By: Relevance
“…Several calix [4] and/or divalent cations (alkaline earth-and transition metal ions) depending on the nature of the chromo/fluorogenic pendant side arms [18,19]. The indoaniline counterpart 3a (Fig.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Several calix [4] and/or divalent cations (alkaline earth-and transition metal ions) depending on the nature of the chromo/fluorogenic pendant side arms [18,19]. The indoaniline counterpart 3a (Fig.…”
Section: Figurementioning
confidence: 99%
“…The respective 1,3-alt 6a,c was prepared following literature method [18]. After detosylation effected by LiAlH 4 , deprotected azacrowns 5a-c and 7a,c were obtained which were then condensed with chloromethylspirobenzopyran 8 [9,11] according to literature analogy to give photochromic molecules 1 and 2 (Scheme 1).…”
Section: Synthesis Of Photochromic Calix[4]azacrowns 1 Andmentioning
confidence: 99%
“…3 More recently, we have reported that a dimeric structure was obtained by reacting 1,3-dipropyl calix [4]arene with N-tosyl tetraethylene glycol dimesylate under basic conditions. 4 Nano-tubes consisting of two [5][6][7] or three 5 calix [4]arene units in the 1,3-alternate conformation were also constructed by linkages at the para position instead of at the phenolic oxygen atoms. We also reported the syntheses of crown ether-capped multimeric calix [4]tubes composed of two, three, four and five 1,3-alternate calix subunits which are linked to each other by diethylene glycol spacers and their binding properties toward metal ions.…”
mentioning
confidence: 99%
“…6 Recently, we have been intrigued by the synthesis of ditopic receptor that is defined with bis-calixazacrown molecule capable of binding two guest ions in the azacrown cavity. [7][8][9][10] For this system we have also tried to synthesize the methoxymethylated compound on the nitrogen atom of the calixazacrown as a precursor of the Mannich product, but the reaction was not accomplished. Interestingly, we then finally found one-pot synthetic method for 2 and 3 as shown in Scheme 1.…”
mentioning
confidence: 99%
“…Our synthesis began with 25,27-bis-(1-propyloxy)calix [4]azacrown-5 (1) which was prepared by following our previous report. 7 Under the nitrogen atmosphere, treatment of 1 with paraformaldehyde and 1,4-hydroquinone in benzene led to 1,3-alternate mono-2 and disubstituted 3 with 2 : 8 ratio calculated by the NMR integration. We obtained 2 and 3 with 8% and 55%, respectively.…”
mentioning
confidence: 99%